PENGARUH BIJI KELOR (Moringa oleifera Lam) SEBAGAI KOAGULAN DARI BERBAGAI KETINGGIAN TEMPAT TUMBUH TERHADAP KUALITAS AIR SUNGAI PALU - Waluyo, Subur; Sangadji, Muh. Nur; Alam, Nur (AGROTEKBIS, 2019)
It aims to determine the effect of moringa seeds as coagulant harvested at various altitudes to grow on water quality of the river and to get the best moringa seeds as coagulant that gives the best effect on the quality of river water hammer. This study uses a completely randomized design (CRD) pattern of the factors that altitude grow consisting of 4 levels of elevation which is 36, 177, 340 and 639 m above sea level. Each treatment was repeated 4 times to obtain 16 experimental units. The data were analyzed statistically using variant analysis (ANOVA). If the treatment shows the real effect or very real continued with Test Honestly Significant Difference (HSD) at level 5 or 1 percent. The results showed that the coagulant moringa seeds were harvested at various altitudes to grow a very real effect on the quality of river water (pH, electrical conductivity, turbidity and total dissolved solids). Coagulant Moringa seeds of altitude grow 36 m above sea level provides the highest percentage increase of the quality of river water that lowers the pH of river water by 8.24, 50.40% electrical conductivity, turbidity 58.91% and 47.39% total dissolved solids